Adoptive transfer of donor B lymphocytes: a phase 1/2a study for patients after allogeneic stem cell transplantation. - Winkler, Julia; Tittlbach, Hannes; Schneider, Andrea; Vasova, Ingrid; Strobel, Julian; Herold, Susanne; Maas, Stefanie; Spriewald, Bernd; Repp, Roland; Kordelas, Lambros; Mach, Michael; Wolff, Daniel; et al. (Blood Advances, 2024)
Immune reconstitution after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is slow and patients carry a high and prolonged risk of opportunistic infections. We hypothesized that the adoptive transfer of donor B cells can foster after HSCT immuno-reconstitution. Here, we report, to our knowledge, the results of a first-in-human phase 1/2a study aimed to evaluate the feasibility and safety of adoptively transferred donor B cells and to test their activity upon recall vaccination. Good manufactoring practice (GMP) B-cell products were generated from donor apheresis products using 2-step magnetic cell separation. Fifteen patients who had undergone allo-HSCT were enrolled and treated after taper of immunosuppression (median, day +148; range, 130-160). Patients received 4 different doses of B cells (0.5 × 106 to 4.0 × 106 B cells per kg body weight). To test the activity of infused donor memory B cells in vivo, patients were vaccinated with a pentavalent vaccine 7 days after B-cell transfer. We observed the mobilization of plasmablasts and an increase in serum titers against vaccine antigens, with a stronger response in patients receiving higher B-cell numbers. Analysis of immunoglobulin VH-sequences by next-generation sequencing revealed that plasmablasts responding to vaccination originated from memory B-cell clones from the donor. Donor B-cell transfer was safe, as no Epstein-Barr virus (EBV) reactivation was observed, and only low-grade graft-versus-host disease (GVHD) occurred in 4 out of 15 patients. This pilot trial may pave the way for further studies exploring the adoptive transfer of memory B cells to reduce the frequency of infections after allo-HSCT. This trial was registered at ClinicalTrial.gov as #NCT02007811.
EVALuna2:562572

Prevention of CMV/EBV reactivation by double-specific T cells in patients after allogeneic stem cell transplantation: results from the randomized phase I/IIa MULTIVIR-01 study - Gerbitz, Armin; Gary, Regina; Aigner, Michael; Moosmann, Andreas; Kremer, Anita; Schmid, Christoph; Hirschbuehl, Klaus; Wagner, Eva; Hauptrock, Beate; Teschner, Daniel; Rösler, Wolf; Spriewald, Bernd; et al. (Frontiers in Immunology, 2023)
Introduction: Allogeneic stem cell transplantation is used to cure hematologic malignancies or deficiencies of the hematopoietic system. It is associated with severe immunodeficiency of the host early after transplant and therefore early reactivation of latent herpesviruses such as CMV and EBV within the first 100 days are frequent. Small studies and case series indicated that application of herpes virus specific T cells can control and prevent disease in this patient population. Methods: We report the results of a randomized controlled multi centre phase I/IIa study (MULTIVIR-01) using a newly developed T cell product with specificity for CMV and EBV derived from the allogeneic stem cell grafts used for transplantation. The study aimed at prevention and preemptive treatment of both viruses in patients after allogeneic stem cell transplantation targeting first infusion on day +30. Primary endpoints were acute transfusion reaction and acute-graft versus-host-disease after infusion of activated T cells. Results: Thirty-three patients were screened and 9 patients were treated with a total of 25 doses of the T cell product. We show that central manufacturing can be achieved successfully under study conditions and the product can be applied without major side effects. Overall survival, transplant related mortality, cumulative incidence of graft versus host disease and number of severe adverse events were not different between treatment and control groups. Expansion of CMV/EBV specific T cells was observed in a fraction of patients, but overall there was no difference in virus reactivation. Discussion: Our study results indicate peptide stimulated epitope specific T cells derived from stem cell grafts can be administered safely for prevention and preemptive treatment of reactivation without evidence for induction of acute graft versus host disease. Clinical trial registration: https://clinicaltrials.gov, identifier NCT02227641.
CRIS-Team Scopus Importer:2023-11-24
Keywords: allogeneic; cytomegalovirus CMV; epitope specificity; Epstein-Barr virus EBV; prevention; reactivation; stem cell transplantation (SCT)

Update on the "Choosing Wisely" initiative in infectious diseases in Germany. - Draenert, Rika; Jung, Norma; Addo, Marylyn; Berner, Reinhard; Bickel, Markus; Bogner, Johannes R.; Cornely, Oliver A.; De With, Katja; Faetkenheuer, Gerd; Hagel, Stefan; Hanses, Frank; Harrer, Thomas; et al. (Infection, 2020)
PURPOSE: The Choosing Wisely® initiative is an international campaign addressing over- and underuse of diagnostic and therapeutic measures in infectious diseases among others. Since 2016, the German Society for Infectious Diseases (DGI) has constantly designed new items in this regard. Here we report the most recent recommendations. METHODS: The recommendations of the DGI are part of the "Klug entscheiden" initiative of the German Society of Internal Medicine (DGIM). Topics for the new items were suggested by members of the DGI, checked for scientific evidence and consented within the DGI and the DGIM before publication. RESULTS: The new recommendations are: (1) individuals with immune-suppression, advanced liver cirrhosis or renal insufficiency should receive a dual pneumococcal vaccination. (2) In case of positive blood cultures with Candida spp. thorough diagnostics and treatment should be initiated. (3) In case of suspected meningitis, adult patients should receive dexamethasone and antibiotics immediately after venipuncture for blood cultures and before potential imaging. (4) In case of suspected meningitis a CT scan before lumbar puncture should not be ordered-except for symptoms indicating high CSF pressure or focal brain pathology or in cases of severe immune-suppression. (5) In patients with suspected severe infections, a minimum of two pairs of blood cultures should be drawn using separate venipunctures prior to antibiotic therapy-regardless of body temperature. There is no need of a minimum time interval in between the blood draws. CONCLUSION: Applying these new Choosing Wisely® recommendations will increase patient safety and the value of health care.
EVALuna2:216771
Keywords: Blood cultures; Choosing Wisely; Infectious diseases; Meningitis; Vaccination